Role of the Electronic Patient Record in the Development of General Practice in the Netherlands - Knottnerus, J. A. (Methods of Information in Medicine, 1999)
From the end of the seventies practice computer systems have been introduced in Dutch general practice. In 1998 90% of the GPs had a practice computer and 60% used it for medical purposes, with good patient acceptance. Collaboration between pioneer GPs, professional organizations, academic institutions and software manufacturers has been of decisive importance. While the practice computer is early recognized as a powerful tool for administrative purposes, it is increasingly supporting clinical and preventive care, quality of care improvement, clinical training of students and vocational training of general practice trainees. Also for scientific research and practice supporting research, automatization has proven to be innovating. Much attention is paid to designing valid databases and database-related research. In addition, practice automatization has opened new perspectives for health policy and management. Further development of technical and methodological issues is needed, and, very importantly, of patients‘ and consumers’ involvement. EPR technology in general practice does not optimally work without good numerator and denominator data, and a good quality patient-doctor relationship over time. While the EPR is a useful tool to facilitate a better performance, it may enable the doctor to focus more on the health care essentials.
Keywords: General Practice; Computer; Research Networks; Quality of Care; Electronic Patient Record